Application of an Integrated Omics Approach for Identifying Host Proteins That Interact With Odontoglossum ringspot virus Capsid Protein - Lin, Pin-Chun; Hu, Wen-Chi; Lee, Shu-Chuan; Chen, Ying-Lan; Lee, Chi-Ying; Chen, Yet-Ran; Liu, Li-Yu Daisy; Chen, Po-Yen; Lin, Shih-Shun; Chang, Ya-Chun (Molecular plant-microbe interactions, 2015)
The glutamic acid at position 100 (E 100 ) in the capsid protein (CP) of Odontoglossum ringspot virus (ORSV) plays an important role in long-distance viral movement in Nicotiana benthamiana. The ORSV E100A mutant, which has a glutamic acid to alanine substitution, shows a loss of systemic infectivity in N. benthamiana. Transmission electron microscopy and size-exclusion chromatography assays showed that E 100 is essential for CP-CP interaction and viral particle assembly. To identify the ORSV triggering or response genes and CP-interacting proteins (CP-IP), an integrated omics approach based on next-generation sequencing and proteomics profiling was used in this study. The whole-transcriptomes of healthy and ORSV-infected leaves of N. benthamiana were analyzed, and the gene information was used to create a N. benthamiana protein database that was used for protein identification following mass spectrometry analysis. The integrated omics approach identified several putative host proteins that interact with ORSV CP WT and were categorized as photosystem subunits, defense-associated proteins, and cell division components. The expression pattern and CP interaction of these CP-IP were examined by semiquantitative reverse transcription polymerase chain reaction and an in vitro binding assay, respectively, to verify the in silico data. Among these proteins, a proteinase inhibitor of N. benthamiana (NbPI2) was highly associated with CP E100A as compared with CP WT , and NbPI1 and NbPI2 were highly induced in ORSV-infected plants. NbPI1- and NbPI2-silenced plants (via a Tobacco rattle virus–induced gene-silencing system) did not exhibit a difference in ORSV infection. Thus, whether NbPI1 and NbPI2 play a role in plant immunity requires further investigation. In summary, the integrated omics approach provides massive and valuable information to identify the ORSV CP-IP and these CP-IP will help us to understand the movement of this virus and plant-virus interaction.